THEORETICAL JUSTIFICATION OF THE DIMENSIONS OF THE PIECES FORMED BY THE VEGETABLE THREADER PUMP STRAIGHTENER - Xamidov , N.M; Eshdavlatov , A.E; Yusupov , F.F (Educational Research in Universal Sciences, 2024)
This article presents the results of the research on the theoretical justification of the size of the seeds formed by the leveler of the seeder, which takes one seed and sows the seeds of vegetable crops in multiple rows.